Prognostic Role of Soluble Programmed Death Ligand 1 in Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Liao, Guixiang; Zhao, Zhihong; Qian, Yuting; Ling, Xiean; Chen, Shanyi; Li, Xianming; Kong, Feng-Ming (Spring) (Frontiers in Oncology, 2021)
Objective: The objective of this study was to explore whether soluble programmed death ligand 1 (sPD-L1) is a potential prognostic biomarker in patients with non-small cell lung cancer (NSCLC). Methods: A comprehensive search of electronic databases was carried out to identify studies assessing the prognostic role of sPD-L1 in NSCLC by July 1, 2021. Hazard ratios (HRs) and 95% confidence intervals (CIs) were applied for data analysis. Results: Eight studies involving 710 patients with NSCLC were included in the analysis. Combined data analysis revealed that high levels of sPD-L1 were correlated with poorer overall survival (HR=2.34; 95% CI=1.82–3.00; P<0.001) and progression-free survival (HR=2.35; 95% CI=1.62–3.40, P<0.001). Subgroup analysis revealed that high levels of sPD-L1 were correlated with a poor overall survival in patients treated with immunotherapy (HR=2.40; 95% CI =1.79–3.22; P<0.001). Conclusion: Published data suggests that sPD-L1 should be further investigated as a potential prognostic factor. Prospective studies with well-designed standard assessment methods should be conducted to validate the prognostic role of sPD-L1 in NSCLC.